Chemical products induce resistance to Xanthomonas perforans in tomato - Itako, Adriana Terumi; Tolentino Júnior, João Batista; Silva Júnior, Tadeu Antônio Fernandes da [UNESP]; Soman, José Marcelo [UNESP]; Maringoni, Antonio Carlos [UNESP] (FapUNIFESP (SciELO), 2015)
The bacterial spot of tomato, caused by Xanthomonas spp., is a very important disease, especially in the hot and humid periods of the year. The chemical control of the disease has not been very effective for a number of reasons. This study aimed to evaluate, under greenhouse conditions, the efficacy of leaf-spraying chemicals (acibenzolar-S-methyl (ASM) (0.025 g.L-1), fluazinam (0.25 g.L-1), pyraclostrobin (0.08 g.L-1), pyraclostrobin + methiran (0.02 g.L-1 + 2.2 g.L-1), copper oxychloride (1.50 g.L-1), mancozeb + copper oxychloride (0.88 g.L-1 + 0.60 g.L-1), and oxytetracycline (0.40 g.L-1)) on control of bacterial spot. Tomatoes Santa Clara and Gisele cultivars were pulverized 3 days before inoculation with Xanthomonas perforans. The production of enzymes associated with resistance induction (peroxidase, polyphenol oxidase, phenylalanine ammonia-lyase, -1,3-glucanase, and protease) was quantified from leaf samples collected 24 hours before and 24 hours after chemical spraying and at 1, 2, 4, 6, and 8 days after bacterial inoculation. All products tested controlled bacterial spot, but only ASM, pyraclostrobin, and pyraclostrobin + metiram increased the production of peroxidase in the leaves of the two tomato cultivars, and increased the production of polyphenol oxidase and -1,3-glucanase in the Santa Clara cultivar.
Keywords: Solanum lycopersicum; Bacterial spot; Control; Enzymes